Biogenic Synthesis of Metal Naroparticles with Antibacterial and Healing Properties for Burn Wound Management - BELKACEMI Basma; BOUTA Yousra; DADDA Aya; MAOUCHE Islam (جامعة الوادي university of eloued, 2026)
In this study, a bimetallic hybrid nanosystem composed of silver (Ag) and zinc (Zn) nanoparticles was synthesized using Animal derived biological material during the preparation process. The synthesized nanoparticles were then incorporated into a suitable pharmaceutical base to obtain a topical therapeutic ointment intended for the treatment of skin burns. Physical characterization results revealed homogeneous nanoparticles with an average size of 19.98 nm, indicating the successful synthesis and good stability of the hybrid nanosystem, The prepared ointment was subjected to several physicochemical evaluations, which demonstrated good homogeneity, suitable stability, and high applicability for topical use. The biological activity of the ointment was also evaluated Brun wound healing using Albino Wistar rats with experimentally induced skin burns. The obtained results showed significant therapeutic efficacy, including accelerated burn wound healing, reduction of inflammation severity, and stimulation of skin tissue regeneration compared to untreated groups, The hybrid nanosystem significantly enhanced the biological performance of the formulation and improved the penetration of the active material into the damaged tissues, leading to higher therapeutic efficiency compared with conventional formulations. The obtained findings confirm that hybrid nanoparticles synthesized using an animal-derived biological material possess promising therapeutic properties, opening new perspectives for the development of modern and effective topical pharmaceutical formulations for burn treatment and skin care.
CD
Keywords: Animal-derived biological material; hybrid nanoparticles; therapeutic ointment; skin burns; wound healing; Brun wound healing.